Model Driven Architecture - Foundations and Applications 5th European Conference, ECMDA-FA 2009, Enschede, The Netherlands, June 23-26, 2009, Proceedings - Paige, Richard F.; Hartman, Alan; Rensink, Arend (Programming and Software Engineering,, 2009)
This book constitutes the refereed proceedings of the 5th European Conference on Model Driven Architecture - Foundations and Applications, ECMDA-FA 2009, held in Enschede, The Netherlands, in June 2009. The 23 revised full papers presented - 16 research papers and 7 industry papers - were carefully reviewed and selected from 72 submissions. Promoting the use of models in the specification, design, analysis, synthesis, deployment, and evolution of complex software systems, the papers address all current issues of model-driven architecture including model transformations, modelling language issues, modelling of behaviour and time, traceability and scalability, model-based embedded systems engineering, and the application of model-driven development to IT and networking systems.